The effect of post-irradiation annealing on the stress corrosion crack growth rate of neutron-irradiated 304L stainless steel in boiling water reactor environment. (December 2019) - Kuang, Wenjun; Hesterberg, Justin; Was, Gary S.
Highlights: PIA has little effect on the CGR of neutron-irradiated 304L SS in NWC. PIA can notably suppress the CGR of neutron-irradiated 304L SS in HWC. The mitigation effect of PIA in HWC correlates with the recovery of Si segregation. PIA is an effective strategy to mitigate IASCC in reducing environment. Abstract: The effect of post-irradiation annealing (PIA) on the irradiation-assisted stress corrosion cracking (IASCC) of 304L stainless steel in boiling water reactor environments was studied. PIA has little effect on the crack growth rate (CGR) in normal water chemistry even it restored most of the irradiation-induced microstructure change. Nevertheless, PIA can significantly suppress the CGR in hydrogen water chemistry (HWC). The mitigation factor of HWC increases with the degree of PIA up to 5 h at 550 °C and correlates with the recovery of Si segregation at grain boundary. PIA is an effective strategy for decreasing IASCC susceptibility in reducing water environment.